Experimental study of operating parameters on the performance of a novel U-type radiant tube with dual flue gas self-circulation structures. (5th May 2022) - Fan, Huanbao; Feng, Junxiao; Xie, Kai; Bai, Wei; Zhao, Yujie; Li, Weidong; Gao, Jun; Liu, Changpeng; Yan, Dongyang; Zhao, Hongyu
Highlights: A novel U-type radiant tube with dual flue gas circulation structures was proposed. Temperature distributions and gas compositions were tested in a 1:1 thermal test. The effects of different operating conditions on the N-URT performance were studied. It produced better heating performance and emission reduction compared with T-URT. The corresponding performance prediction equations of key parameters were obtained. Abstract: Faced with the challenges of gas-fired radiant tube performance improvement and increasingly stringent environmental requirements, we proposed a novel U-type radiant tube (N-URT) with dual flue gas self-circulation structures for heat treatment furnaces. A 1:1 scale experimental system was established to evaluate heating characteristics of the N-URT under different operating conditions. The effects of input power ( P ) and excess air coefficient ( α ) on temperature uniformity, NOx emission and thermal efficiency were analyzed and discussed in-depth. It was found that the N-URT can significantly improve the heating performance compared to conventional U-type radiant tube. As P increased from 35 to 50 kW, the maximum wall temperature difference decreased from 86.9 to 63.2 °C, the thermal efficiency dropped from 92.7% to 89.1%, and the outlet NOx emission increased from 89.6 to 103.6 mg·m −3 @8% O2 . As α increased, the temperature uniformity increased, but the heat recovery and NOx reduction decreased. In addition, the effect of P on NOx emission and maximum wall temperature difference was more significant than α, indicating that the air supply strategy for a given P should be carefully considered. Accordingly, the experimental results can provide a theoretical guidance for the development and application of the radiant tube.